Խուան Կարլոս Օնետտիի «Անդունդը» վիպակի և ֆրանսիական էկզիստենցիալիզմի որոշ առնչություններ - Մարինե Կիրակոսյան (ՀՀ ԳԱԱ հրատ.)
Схожесть романов «Бездна» Хуана Карлоса Онетти и «Тошнота» Жан-Поля Сартра очевидна в латиноамериканской литературе, но тщательно не изучена. The similarity between Juan Carlos Onetti’s novella, "The Pit" and Jean-Paul Sartre’s novel "Nausea" has already been observed by Latin American critics but has not yet been thoroughly analyzed.
Keywords: Language and Literature